Long-term effects of microplastics on the behaviour and physiology of reef-building corals - Rades, Sven Marvin; Justus Liebig University Giessen (My University, 2024)
Coral reefs are declining because of anthropogenic pressures, but the role of ubiquitous microplastic pollution is unclear. Microplastics affect reef-building corals mostly at high concentrations, while effects are often attenuated at lower environmentally relevant concentrations. However, the scarcity of long-term exposure data hinders the assessment of microplastic stress, its causes, and coral behavioural and physiological acclimation over time. Therefore, this thesis aimed to infer acclimation mechanisms from long-term effects of microplastics on coral behaviour and physiology. For this, the four common reef-building coral species Acropora muricata, Pocillopora verrucosa, Porites lutea, and Heliopora coerulea were exposed to a realistic microplastic concentration (i.e., 200 polyethylene particles L-1) in a controlled long-term aquarium experiment. After 11 months, energy reserves, metabolites, growth, and photosymbiont state were analysed. After 15 months, feeding rates on microplastics and natural food (i.e., Artemia sp. cysts), feeding discrimination (i.e., ratio of feeding on microplastics and natural food), and reactions to both were determined in a 24-hour pulse exposure. Although long-term exposed to microplastics, results showed that corals did not change their feeding, discrimination, and defence behaviour to reduce microplastic uptake. Therefore, it is assumed that the corals did not use, or lacked, behavioural acclimation mechanisms, such as heterotrophic plasticity, to mitigate long-term microplastic stress. Despite this absence of behavioural acclimation, coral physiology was only marginally affected, as occasional species-specific effects may indicate physiological acclimation mechanisms. Increased taurine levels, reduced growth, and altered photosynthetic efficiency in corals are likely to mitigate microplastic stress at environmentally relevant concentrations where coral photosymbiosis remains intact. However, under scenarios with predicted increases in microplastic concentration and other cumulative anthropogenic stressors, acclimation through compensatory mechanisms may be limited, likely exacerbating adverse effects on coral health. Overall, this thesis has provided unprecedented insights into long-term acclimation mechanisms that may help corals cope with relevant microplastic concentrations and has contributed to a more holistic understanding of coral stressor susceptibility, which is needed to guide conservation efforts to curb coral reef decline. However, these coral acclimation mechanisms may be challenged by the combined effects of multi-polymer microplastics and other anthropogenic stressors, an open question for which this work provides a starting point for future research.
Langzeiteffekte von Mikroplastik auf das Verhalten und die Physiologie riffbildender Korallen
Keywords: microplastics; reef-building corals; long-term exposure; ingestion; feeding rate; energy reserves; physiology; photosynthesis; acclimation; ddc:590; ddc:570